Aspek Hukum Pengelolaan Limbah Industri pada PT Selatan Jadi Jaya dalam Perspektif Perlindungan Lingkungan - Muhammad Zidan Gani; Nur Qoilun (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Industrial waste management is an essential part of environmental protection and management efforts in Indonesia. Industrial development contributes positively to economic growth, but it also creates risks of environmental pollution when waste is not managed properly and in accordance with legal regulations. This study aims to analyze legal regulations concerning industrial waste management in Indonesia, evaluate the compliance level of PT Selatan Jadi Jaya with applicable laws and regulations, and examine law enforcement efforts and accountability mechanisms for violations affecting the environment. The research applies an empirical normative method using statutory and field approaches. Data were collected through literature studies of legislation, scientific journals, and legal doctrines, supported by observations and interviews with related parties. The findings show that industrial waste management has been comprehensively regulated under Law Number 32 of 2009 and Government Regulation Number 22 of 2021. However, implementation still encounters obstacles such as weak supervision, limited legal awareness among business actors, and economic considerations affecting corporate compliance. PT Selatan Jadi Jaya has fulfilled several administrative obligations but still requires improvement in substantive waste management practices. Effective supervision, consistent law enforcement, and stronger corporate commitment to sustainability and environmental responsibility are therefore necessary to achieve optimal environmental protection.